Características morfogênicas da pastagem de sorgo forrageiro submetido ao pastejo contínuo de novilhos de corte suplementados - Martini, Ana Paula Machado (2015)
Feed supplementation of the animals affects the pasture intake and may influence its productive and structural characteristics. Morphogenesis is a valuable tool for the dynamics understanding of the pasture, however the morphogenetic studies related to sorghum culture are still scarce as well as the evaluation of the supplementation effects on these characteristics. The objective of the present study was to evaluate the effects of the different levels of supplementation on the morphogenetic characteristics of sorghum forage (Sorghum bicolor (L.) Moench) submitted to continuous grazing of beef steers. The experiment was performed at the Beef Cattle Laboratory of UFSM from January to April, 2013. Morphogenetic measures were taken by the marked tiller technique in order to determine the morphogenetic variables of sorghum forage. The completely randomized experimental design was used, with measures repeated in time, with three treatments and two repetitions (area) for the morphogenetic characteristics. The results of the morphogenetic variables were submitted to variance analysis with 5% of significance level using PROC MIXED. The analyses were performed with the assistance of the statistical package SAS 9.1.3 (2009). By increasing the supplementation level offered to the animals it was observed a lower value for the Number of Live Leafs (2.77, 3.34 and 3.55) and Leaf Elongation Rate (0.06, 0.09 and 0.08) characteristics. The variables Leaf Appearance Rate (0.0041, 0.0043 and 0.039), Leaf Senescence Rate (0.05, 0.06 and 0.11) and Phyllochron (283.96, 265.21 and 278.62) were not influenced by the different supplementation levels. There was a difference among the evaluation periods for the characteristics Leaf Life Span (1081.1, 986.25 and 788.79) and Leaf Elongation Length (350.58, 312.83 and 326.36). For the characteristics Canopy Height, Pseudo Stem Length, and Final Length of Blades there was an interaction between treatment and period.